Influence of B4C powder reinforcement on coating structure, microhardness and wear in friction surfacing - Ozler, Latif; Tosun, Gul; Ozcan, Mehmet Erbil (Taylor & Francis Inc, 2020)
In this paper, the coating structure, microhardness and wear resistance of the coatings fabricated by the friction surfacing method was investigated. AA5754 substrate was coated by using two different methods, namely friction surfacing with powder sintering and powder laying. In the powder sintering method, first, the boron carbide (B4C) and the aluminum (Al) powder mixture at certain ratios were pressed by filling into a AA7075 consumable rod. Next, they were sintered. Then, the substrate was gradient coated by using the prepared consumable rod with the friction surfacing method. In the powder laying method, a certain amount of only B4C powder was laid on the substrate surface and then the substrate was coated with B4C by using a powder-free AA7075 consumable rod moving over the substrate. As a result, the wear resistance and hardness in the gradient coatings were significantly improved than compared to the substrate as the amount of reinforcement increased in the powder sintering method. In the coatings of the powder laying method, the adhesion surface between the substrate and the coating layer was good enough but non-homogeneous. The wear resistance and hardness in the coatings of the powder laying were not good compared to the gradient coatings.
Keywords: Friction; surfacing; coating; aluminum; boron; microstructure; microhardness; wear